2021
DOI: 10.1039/d0tc04881j
|View full text |Cite
|
Sign up to set email alerts
|

Extended ligand conjugation and dinuclearity as a route to efficient platinum-based near-infrared (NIR) triplet emitters and solution-processed NIR-OLEDs

Abstract: A complex in which two Pt(ii) ions are cyclometallated to bis-dithienylpyrimidine displays intense luminescence in the NIR region, both in solution and in an OLED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 70 publications
2
49
0
Order By: Relevance
“…Instead, it appears that the two metals benefit the complex by provision of additional singlet states involving metal d orbitals that are different from those of T 1 , while also bringing them closer together. 8,9,42 The ancillary iodide acts in a similar way in complex 3 , by destabilising HOMOs and reducing energy difference between HOMO and HOMO−1 etc. In extreme situations, this also leads to re-ordering of orbital patterns, which promotes even stronger SOC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, it appears that the two metals benefit the complex by provision of additional singlet states involving metal d orbitals that are different from those of T 1 , while also bringing them closer together. 8,9,42 The ancillary iodide acts in a similar way in complex 3 , by destabilising HOMOs and reducing energy difference between HOMO and HOMO−1 etc. In extreme situations, this also leads to re-ordering of orbital patterns, which promotes even stronger SOC.…”
Section: Resultsmentioning
confidence: 99%
“…1,7 Recently, it has been found that the use of dinuclear structures -featuring two metal ions -may lead to larger SOC and accelerated triplet radiative rate constants relative to structurally comparable mononuclear complexes. [8][9][10] Meanwhile, the decay rates of organometallic complexes may also be increased if they exhibit thermally activated delayed fluorescence (TADF). 11,12 This phenomenon relies on the up-conversion of triplets into singlets (T 1 -S 1 ) and thus benefits from the high singlet radiative rates (S 1 -S 0 ) rather than relying on the promotion of the triplet radiative rate constant (T 1 -S 0 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are also supported by recent literature data. 17,18,34,36,60 These parameters directly affect TADF and therefore it is crucial to understand their role in the mechanism. ΔE ST : Figure 8a shows simulations of the luminescence lifetime obtained using eq.…”
Section: Effect Of Kinetic Parameters On Tadfmentioning
confidence: 99%
“…The multinuclear molecular structure of transition metal complexes has been shown as a very promising approach to enhance the phosphorescence rate. 1–6 Indeed, complexes of Ir( iii ) 7–9 and Pt( ii ) 10,11 featuring dinuclear structures often have several times faster phosphorescence compared to their mononuclear analogues. This effect is due to the enhanced spin–orbit coupling (SOC) of the lowest (emitting) triplet state (T 1 ) with singlet states (S 0 ).…”
Section: Introductionmentioning
confidence: 99%
“…This effect is due to the enhanced spin–orbit coupling (SOC) of the lowest (emitting) triplet state (T 1 ) with singlet states (S 0 ). 8–10 The photophysical properties of such materials are readily tuned in a wide range via alteration in bridging and auxiliary ligands. For instance, depending on the structure of the bridging ligand, the photoluminescence of the complex may vary from ultrafast phosphorescence 8,12 to dual emission 13 consisting of slow phosphorescence accompanied by fluorescence.…”
Section: Introductionmentioning
confidence: 99%